EXPLOITATION OF RESOURCES OF MARINE SHARKS IN THE WATERS FROM QUANG NGAI TO BINH THUAN PROVINCES - Long, Nguyen Van; Tuan, Vo Si (Vietnam Journal of Marine Science and Technology, 2012)
Studies on exploitation of marine sharks were conducted by interview and consultation with local fishing villages in six provinces including Quang Ngai, Binh Dinh, Phu Yen, Khanh Hoa, Ninh Thuan and Binh Thuan. A total of 180 fishers of some major fishing gears were interviewed and consulted in 2010 and 2011. Results from interview and consultation show that there were 530 boats fished marine sharks with the highest number being found in Binh Thuan (181 boats), Binh Dinh (140 boats), Khanh Hoa (98 boats), Phu Yen (74 boats), Quang Ngai (32 boats) and Ninh Thuan (5 boats). There were six major fishing gears to fish marine sharks (shark longline fishing, tuna longline fishing, purse seine and hookah diving) at 3 major fishing grounds: 1) the coastal waters of Quang Ngai, Binh Dinh and Phu Yen; 2) the area surrounding Bo Kham - Spratly island - offshore Vung Tau; and 3) the area adjacent to Malaysia, Brunei and Indonesia with the major fishing season occurred from February to October. A total of 13 species of marine sharks were caught with mean catch per boat of shark longline fishing being highest (0.53 ton/boat/month), purse seine (0.50 ton/boat/month) and tuna longline fishing (0.18 ton/boat/month), of which Alopias pelagicus and Sphyrna lewini were dominant. In 2010, total catch was about 1,130 tons/year, with the highest being recorded to sharks longline fishing (1,126 tons/year). Some major provinces supported higher catch were Binh Thuan (886 tons/year), Binh Dinh (201 tons/year) and Phu Yen (186 tons/year). In general, there was a decline in number of fishing boats (from 16.7 to 85.8%), catch per boat (from 14.4 to 83.8%) and total catch (from 58.4 to 99.4%) of each fishing gear between the period of 10 years before and 2010 in each province. This indicates that resources of marine sharks were over-exploited, especially in the coastal waters of Vietnam.